THE INFLUENCE OF THE REALISTIC MATHEMATICS EDUCATION (RME) APPROACH ASSISTED BY THE PLSV BOARD ON THE MATHEMATICAL LITERACY ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - lia kurniawati; Amelia Nur Oktaviani; Otong Suhyanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
Mathematical literacy ability is one of the abilities that students must have. Mathematical literacy ability includes the ability to understand, use, and apply mathematical concepts and procedures in various situations, both in academic contexts and in everyday life. This study aims to analyze the effect of the Realistic Mathematics Education (RME) Approach Assisted by the PLSV Board on mathematical literacy ability. This research was conducted at one of the junior high schools in Tangerang City in the odd semester of the 2024/2025 academic year. This study used a quasi-experimental method with a randomized posttest only control design involving 30 students in the experimental group and 32 students in the control group. Data collection on mathematical literacy ability used a test instrument in the form of seven descriptive questions that had been tested for validity, reliability, discriminatory power and level of difficulty first. The indicators of mathematical literacy ability studied were formulate, employ and interpret. The results of the study showed that the mathematical literacy skills of students in the experimental class whose learning used the Realistic Mathematics Education (RME) Approach Assisted by the PLSV Board were higher than those in the control class whose learning used the scientific approach.